Parameterization of the propeller thrust for modelling ship braking in ice channel behind icebreaker. Issue 1 (21st December 2022) - Goncharov, Vadim K; Klementieva, Natalia Yu
Abstract: Cargo ship sailing within the ice channel that an assisting icebreaker tracks in the compact ice cover is the usual navigation practice for difficult ice conditions in freezing seas and Arctic water areas. When the icebreaker or an ahead vessel stops before the insuperable ice obstacle or because of engine trouble, the danger of an emergency appears, namely of collision with the icebreaker or the ahead ship, if the interval between them is not sufficient for effective braking and stopping. The paper presents the equation that describes the ship braking process within an ice channel and includes the thrust of the propeller that works under the reverse regime. The specific of this regime is the following: the ship continues the motion 'forwards' and the propeller rotates 'backwards'. An analytical method for description of the ship propeller work on the reverse regime is absent because of the detached flow on its blades. The paper describes the developed empirical method of this regime parameterization on the basis of serial models of propeller testing. The outcomes of this investigation are applied to a ship braking process simulation and the evaluation of the safe interval between the ship and the icebreaker.